Application of nanoparticle mediated N-arylation of amines for the synthesis of pharmaceutical entities using vit-E analogues as amphiphiles in water1. Issue 26 (22nd March 2015) - Kumar, Atul; Bishnoi, Ajay Kumar
<x xml:space="preserve">Abstract</x> The first CuI-nanoparticle catalyzed inter and intramolecular N-arylation of amines using vitamin E analogues as amphiphiles was developed in water and is extended to azoles, substituted indoles, a bioactive natural product and intermediates of pharmaceutical entities.